Voices of the Pacific : untold stories from the Marine heroes of World War II - Makos, Adam; Brotherton, Marcus (Dutton Caliber, an imprint of Penguin Random House LLC, 2021)
Following fifteen Marines from Pearl Harbor, through their battles with the Japanese, to their return home after V-J Day, Adam Makos and Marcus Brotherton have compiled an oral history of the Pacific War in the words of the men who fought on the front lines. With vivid, unforgettable detail, these Marines reveal harrowing accounts of combat with an implacable enemy, the camaraderie they found, the friends they lost, and the aftermath of the war's impact on their lives. With unprecedented access to the veterans, rare photographs, and unpublished memoirs, Voices of the Pacific presents true stories of heroism as told by such World War II veterans as Sid Phillips, R.V. Burgin, and Chuck Tatum--whose exploits were featured in the classic HBO miniseries The Pacific--and their Marine buddies from the legendary 1st Marine Division.